2016
DOI: 10.1371/journal.pone.0150133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cellular Pathway Disturbances on Misfolded Superoxide Dismutase-1 in Fibroblasts Derived from ALS Patients

Abstract: Mutations in superoxide dismutase-1 (SOD1) are a common known cause of amyotrophic lateral sclerosis (ALS). The neurotoxicity of mutant SOD1s is most likely caused by misfolded molecular species, but disease pathogenesis is still not understood. Proposed mechanisms include impaired mitochondrial function, induction of endoplasmic reticulum stress, reduction in the activities of the proteasome and autophagy, and the formation of neurotoxic aggregates. Here we examined whether perturbations in these cellular pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…Increased oxidative stress at initial stages of neurotoxic conditions is also associated with activation of autophagylysosomal system [55,56] that could be beneficial and protective per se. Meanwhile, Pickford et al have shown decreased autophagy in addition to accelerated Ab aggregation in the brain of mice model of AD [57].…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress at initial stages of neurotoxic conditions is also associated with activation of autophagylysosomal system [55,56] that could be beneficial and protective per se. Meanwhile, Pickford et al have shown decreased autophagy in addition to accelerated Ab aggregation in the brain of mice model of AD [57].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have utilized ALS patient-derived dermal fibroblasts as an in vitro model to study misfolding under physiological SOD1 expression levels (Keskin et al, 2016). Cells cultured in vitro are typically maintained in humidified ambient air supplemented with 5% (v/v) CO 2 , resulting in an O 2 tension of approximately 19%.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study of patient-derived fibroblasts showed that misfolded SOD1 is primarily degraded by the proteasome (Keskin et al, 2016). However, exposure to low O 2 tension did not lead to a reduction in proteasome activity in MNAC extracts (Fig EV3C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations